Pemaknaan Audiens Pada Seniman Cross-Gender Dalam Dokumenter Lelaki Ayu Primadona Jawa: Lengger Lanang - Afinada Aulia Agani Agani; Safira Nur Ujiningtyas; Rahmawati Zulfiningrum (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2026)
This documentary film entitled Lelaki Ayu Primadona Jawa: Lengger Lanang discusses the artist Lengger Lanang who changes his appearance into a woman while dancing. This dance is usually called cross-gender, but Lengger Lanang is threatened with extinction because of public stereotypes about LGBT or the sexual orientation of Lengger Lanang dancers, even though they are two different things. This study aims to describe the audience's reception of cross-gender artists in the documentary using Stuart Hall's encoding-decoding. Informants are divided into three groups of reader positions: dominant, negotiating and opposition. This type of research is descriptive qualitative which focuses on the reading position by analyzing the audience's understanding of cross-gender artists through documentary film scenes. The data were obtained from in-depth interviews. The results showed from seven informants, there were four informants were in a dominant position and three informants were in a negotiating position, also there was no audience in an opposition position. The reading position of the audience is influenced by the background of the audience who watched the documentary. The audience interprets this documentary as an understanding of cross-gender artists but also discusses the preservation of culture, history, and values ​​owned by Lengger Lanang dancers in Banyumas